UJI AKTIVITAS SITOTOKSIK SENYAWA 7-O-PROPIL 3â,4â- DIMETOKSIISOFLAVON HASIL SINTESIS PADA KULTUR SEL KANKER PAYUDARA MCF-7 DAN T47D - , ELFIAN YOGY FISTA, Dra. Sri Herwiyanti,M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Cancer is an illness with high incidence and high morbidity. Isoflavon is a compound of natural substance that can prevent many kind of chronic illness, especially cancer. A compound of 7-O-Propil 3â, 4â Dimethoxyisoflavon is a new compound which is derived from isoflavon, but the cytotoxic activity of this compound on cancer cell is not known. Objective: This experiment was intended to know the cytotoxic activity of 7-O-Propil 3â, 4â Dimethoxyisoflavon which is isoflavone derivate compound on cell line culture of breast cancer MCF-7 and T47D. Method: This research was a quasi-experimental study using cell line culture of breast cancer MCF-7 and T47D. The experimental group was 7-propa ISR while doxorubicin was the control group. Cytotoxicity test used MTT assay method. Experimental compound in various concentration 6,25